Os Fundos de Investimento Imobiliário Residenciais : transformações no segmento e formas de atuação no contexto da financeirização do cotidiano (2017–2023) - Valfré, Lorenzo Gonçalves (2025)
Since the half of the 2010s, we have noticed an unprecedented connection between the financial markets and increasingly larger segments of the general population, shaping part of a broad process of the financialization of daily life in Brazil. In this context, due to their characteristics, particularities, and promotion, real estate investment trusts (called Fundos de Investimento Imobiliário – FIIs) have grown in popularity, expanding their economic power and adding complexity to their operational strategies, aiming to attract resources from new investors and broaden their real estate-financial accumulation fronts. During the same period, FIIs have increasingly become part of the strategic portfolio of real estate developers, leading to significant transformations in the capitalist production of housing. This study aims to understand how this process of financialization of daily life has influenced specifically the residential segment of FIIs in terms of their modes of operation, organization, and relationships with real estate agents. Using data primarily provided by the Comissão de Valores Mobiliários (CVM) about the real estate fund industry from 2017 to 2023, we identified a strong proportional growth of the residential segment of FIIs and transformations in their operational and organizational structures, particularly aimed at attracting small investors' capital. On one hand, there is an intensification of these funds as real estate developers due to their increasing economic power. On the other hand, we observe the use of FIIs as part of new strategies by established real estate developers to execute their accumulation processes, particularly within the residential rental segment. The financial relevance and the rapid growth of this segment in recent years, as well as the way it has unfolded, lead us to conclude that such expansion was only possible due to this specific dimension of financialization – namely, the financialization of daily life. This underscores the continuous need to understand the relationship between this dimension and its implications for the real estate sector.